A Systematic Review of Culturally Responsive Teaching in Global and Indonesian Contexts - Slamet Setiawan; Nabila Putri Rahmadani; Hanafi Hanafi (ELLITE: Journal of English Language, Literature, and Teaching, 2026)
Culturally Responsive Teaching (CRT) has gained increasing attention as a pedagogical approach aimed at promoting equity and inclusivity in diverse educational settings. This study presents a Systematic Literature Review (SLR) that examines the implementation of CRT practices across global contexts and in Indonesia, with a particular focus on teaching strategies and contextual adaptations. Drawing on selected empirical studies, the review categorizes CRT practices into three key implementation strategies: creating inclusive curriculum and content, cultivating cultural competence and awareness among educators, and fostering positive teacher–student relationships. Findings indicate that, globally, CRT is implemented through curriculum indigenization, decolonization, and the promotion of critical consciousness, often supported by structured professional development. In contrast, CRT in Indonesia emphasizes contextualization, localization of content, and student-centered learning across educational levels. While these practices enhance relevance and engagement, they remain largely classroom-focused and show limited attention to structural inequalities. This study identifies a gap between global and Indonesian implementations, particularly in the depth of critical engagement. It suggests the need for more comprehensive approaches that integrate cultural relevance with critical and systemic dimensions to strengthen CRT practices in Indonesia.